t-37+t=t+30

Simple and best practice solution for t-37+t=t+30 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for t-37+t=t+30 equation:


Simplifying
t + -37 + t = t + 30

Reorder the terms:
-37 + t + t = t + 30

Combine like terms: t + t = 2t
-37 + 2t = t + 30

Reorder the terms:
-37 + 2t = 30 + t

Solving
-37 + 2t = 30 + t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-1t' to each side of the equation.
-37 + 2t + -1t = 30 + t + -1t

Combine like terms: 2t + -1t = 1t
-37 + 1t = 30 + t + -1t

Combine like terms: t + -1t = 0
-37 + 1t = 30 + 0
-37 + 1t = 30

Add '37' to each side of the equation.
-37 + 37 + 1t = 30 + 37

Combine like terms: -37 + 37 = 0
0 + 1t = 30 + 37
1t = 30 + 37

Combine like terms: 30 + 37 = 67
1t = 67

Divide each side by '1'.
t = 67

Simplifying
t = 67

See similar equations:

| 4h-70=12h+2 | | -7.678+(-29)= | | 8.3x-18=9x | | 14y-13y=13 | | (5x-7)+(3x+8)= | | (u-7)*10=70 | | -3/4a | | 45x^4-100x+55=0 | | g-1= | | g(x)=5x+65 | | 2y^2-4y-20=0 | | 2x-8+5x-32=180 | | 3a+6+4= | | 2x-6+90+48=180 | | (q+7)*5=45 | | 90+y+2+3y=180 | | g(x)=-4x+15 | | 50-4x=-61-6x | | 7m-6m=4 | | 4+[7-m]=5 | | (5*5)+(b*b)=(16*16) | | 25x-27x=7-9 | | 5k-4k=6 | | 3x-5=7k+7 | | 2x+2=4x+2+x | | g(x)=-4x+30 | | 11+2lnx=4 | | 3(c-9)=3 | | 2c^4-6c^3=12c^2+36c | | 3x+3x-7=65 | | K+20=7 | | x+90+x+4=180 |

Equations solver categories